PENANGANAN BALITA STUNTING PADA KELUARGA DI WILAYAH KERJA PUSKESMAS SUKORAME KOTA KEDIRI - Indah Rahmaningtyas, Indah (Jurnal Informasi Kesehatan Indonesia (JIKI), 2020)
Stunting is a chronic condition that describes stunted growth due to long-term malnutrition. The results of Basic Health Research in Indonesia in 2010 showed that the discovery of short toddlers by 35.6%, although the prevalence of undernutrition and malnutrition had decreased from 18.4% in 2007 to 17.9% in 2010. This percentage meant more than one-third of toddlers have lower height than the standard height of toddlers of their age. This study aims to determine the description of the family in handling stunting in their toddlers in the Sukorame Public Health Center Work Area in City of Kediri. This research is a descriptive study with a qualitative approach. Participants in this study were a number of families with stunting toddlers as many as 6 participants. Data collection uses a process of in-depth interviews (in depth interviews), Focus Group Discussion (FGD) and observation of handling stunting by the family. The results showed that families with short toddlers (stunting), most of them have low education, middle-low socio economic status, and in specific nutrition interventions and families sensitive to stunting are still below health standards. Need attention from cooperation both the government with cross-sectoral activities and cross-programs and the community by increasing social sensitivity.